The unprecedented epidemic-like scenario of dermatophytosis in India: I. Epidemiology, risk factors and clinical features - Verma, Shyam B; Panda, Saumya; Nenoff, Pietro; Singal, Archana; Rudramurthy, Shivprakash M; Uhrlass, Silke; Das, Anupam; Bisherwal, Kavita; Shaw, Dipika; Vasani, Resham (Indian journal of dermatology, venereology, and leprology, 2021)
Dermatophytosis has attained unprecedented dimensions in recent years in India. Its clinical presentation is now multifarious, often with atypical morphology, severe forms and unusually extensive disease in all age groups. We hesitate to call it an epidemic owing to the lack of population-based prevalence surveys. In this part of the review, we discuss the epidemiology and clinical features of this contemporary problem. While the epidemiology is marked by a stark increase in the number of chronic, relapsing and recurrent cases, the clinical distribution is marked by a disproportionate rise in the number of cases with tinea corporis and cruris, cases presenting with the involvement of extensive areas, and tinea faciei.